(untitled) (Advances in Knowledge Representation, 2021)
This paper proposes a case study to analyze the process of information retrieval and the searching as a learning process in a search environment about Covid-19. As research methodology, the work analyzes a group of participants, checking your level of knowledge about Covid-19, before and after a web search. The study includes an analysis of the Dunning-Kruger effect, metacognitive experiences, and use of queries on the web. The findings of this research corresponds the observation of a similar pattern on the tests realized with the Dunning-Kruger effect, and also an increase in the estimate of grades in the second test in the highest grades in a population with different educational levels and age groups. It is observed even when the users browser the same queries, still there are difficulties and limitations in the advancement knowledge in the search environments. It is important highlighted this research analyzed a specific situation, that involve information about Covid-19, interest of people of different schooling and age, as well as the large volume of information, fake news, and difficulties in analyzing information, unlike experiments in other analyzed researches. At the end, this case study opens the door to new focuses and opportunities for experimentation in the process of information retrieval.